PENGUJIAN EFEK PEMBINGKAIAN DAN LOCUS OF CONTROL SEBAGAI DETERMINAN ESKALASI KOMITMEN DALAM KEPUTUSAN INVESTASI (Studi Kasus Pada Perusahaan Manufaktur Di Kota Semarang) - Bahrudin, Saiful; Anissa, Nur (PRESTASI, 2011)
A rational decision-making based on economics theory assumes that a manager tries to increase the companyâs profit. Indeed, a manager shall be able to make an optimal decision. Moreover, a manager has to put an investment for the project work that bring profit to the company, and to periodically assess the aspect of economic work on that project. Furthermore, in a real-business word, an under-indicated failed project but still in progress to be continued indicates as an escalation commitment. Meanwhile, a framing is considered as one of the factors causing the escalation commitment, and is how an information or fact is being revealed. At the same time, locus of control is also the factor causing this escalation commitment. Locus of control is the way how someone sees an event; whether he/she is able to control it or not. The aim of this thesis is to study the direct influences of framing and locus of control. The writer uses two ways analysis of variance as his analytic technique. The result of the study shows that there is s positive influence towards the escalation commitment: a signification p=0,000 or p<0,05 for variable on framing, and the same variable for locus of controlKeywords: framing, locus of control, and escalation commitment